Preprints in Chemistry: a Research Team's Journey** - Dr. Rosaria Ciriminna; Dr. Mario Pagliaro (ChemistryOpen, 2023)
Abstract The benefits of publishing research papers first in preprint form are substantial and long‐lasting also in chemistry. Recounting the outcomes of our team's nearly six‐year journey through preprint publishing, we show evidence that preprinting research substantially benefits both early career and senior researchers in today's highly interdisciplinary chemical research. These findings are of general value, as shown by analyzing the case of four more research teams based in economically developed and developing countries.